Effects of interventions on use of hearing protectors among farm operators: A randomized controlled trial. (12th February 2016) - McCullagh, Marjorie C.; Banerjee, Tanima; Cohen, Michael A.; Yang, James J.
Abstract: Objective : The purpose of this study was to compare the effectiveness of three interventions designed to promote hearing protector device (HPD) use. Design : Randomized controlled trial. Study sample : Farm operators (n = 491) were randomly assigned to one of five intervention groups: (1) interactive web-based information with mailed assortment of HPDs; (2) Interactive web-based information only; (3) static web-based information with mailed assortment of HPDs; (4) Static web-based information only; or (5) mailed assortment of HPDs only. Data were analysed using a mixed model approach. Results : HPD use increased among all participants, and increased more among participants receiving the mailed HPDs (with or without information) compared to participants receiving other interventions. Participants receiving the interactive web-based information had comparable increased use of HPDs to those receiving the static web-based information. Participants receiving the mailed HPDs had more positive situational influences scale scores than other participants. Program satisfaction was highest among mailed and web-based information groups. Conclusions : A mailed assortment of hearing protectors was more effective than information. Interactive and static information delivered via web were similarly effective. Programs interested in increasing HPD use among farmers should consider making hearing protectors more available to farmers.